Secondary Prevention Medical Therapy and Outcomes in Patients With Myocardial Infarction With Non-Obstructive Coronary Artery Disease - Paolisso, Pasquale; Bergamaschi, Luca; Saturi, Giulia; D'Angelo, Emanuela Concetta; Magnani, Ilenia; Toniolo, Sebastiano; Stefanizzi, Andrea; Rinaldi, Andrea; Bartoli, Lorenzo; Angeli, Francesco; Donati, Francesco; Rucci, Paola; et al. (Frontiers in Pharmacology, 2020)
Background: Myocardial infarction with non-obstructive coronary arteries (MINOCA) is a heterogeneous entity with relevant long-term major cardiovascular events. Several trials have demonstrated that dual antiplatelet therapy (DAPT), β-blocker, renin-angiotensin-aldosterone system (RAAS) inhibitor and statin therapy improve the prognosis in patients with obstructive myocardial infarction (ob-MI). However, evidence on the best medical therapy for secondary prevention in MINOCA patients is lacking. Purpose: To investigate the effects of secondary prevention treatments at discharge on mid-term outcomes in MINOCA. Methods: Patients with acute myocardial infarction (MI) undergoing early coronary angiography between 2016 and 2018 were extracted from a clinical database. The diagnosis of MINOCA was made according to 2016 ESC MINOCA Position Paper criteria. Second-level diagnostic work-up including cardiac magnetic resonance was performed to exclude non-ischemic troponin elevation cause. The relationship between treatments and outcomes was evaluated by using Kaplan-Meier survival analysis and Cox regression models. All confirmed MINOCA were followed in our outpatient clinics. The primary end-points were all-cause mortality, re-hospitalization for MI and a composite outcome including all-cause mortality, hospitalization for MI and ischemic stroke (MACE). Results: Out of 1141 AMI who underwent coronary angiography, 134 were initially diagnosed as MINOCA. Patients with MINOCA were less likely to receive secondary prevention treatments than patients with obstructive coronary artery disease (CAD) MI (respectively, 42.1%vs81.8% for DAPT; 75.5%vs89.6% for β-blockers; 64.7%vs80.3% for RAAS inhibitor and 63.9%vs83% for statins). Based on the diagnostic work-up completed during the first month after discharge, a final sample of 88 patients had confirmed MINOCA. During an average follow-up of 19.35±10.65 months, all-cause mortality occurred in 11(12.5%) patients, recurrence of MI in 4(4.5%), and MACE in 15(17.0%) patients. Patients treated with RAAS inhibitors and statins had a significantly longer survival. On the contrary, no increase in survival was found in patients treated with β-blockers or DAPT. Cox multivariable analysis, including all secondary prevention drugs, showed that only RAAS inhibitors were associated with reduced all cause-mortality and MACE. Conclusion: This prospective study suggests that RAAS inhibitor therapy provides mid-term beneficial effects on outcomes in MINOCA patients; in contrast, DAPT, β-blocker and statin therapy had no effects on mortality and MACE.